Spontaneous transitions of actin-bound tropomyosin toward blocked and closed states - Kiani, Farooq Ahmad; Fischer, Stefan (The journal of general physiology, 2019)
After muscle contraction, myosin cross-bridge heads detach from thin actin filaments during relaxation. Structural and kinetic data of cross-bridge-thin filament interactions have shown that tropomyosin’s position on F-actin is biased toward the blocked or closed states when myosin detaches. It is not clear if structural linkages between tropomyosin and myosin cross-bridge heads, or tropomyosin and Ca2+-free troponin, drive the process or whether tropomyosin movement is energetically independent of myosin and troponin influence. Here we provide in silico data about tropomyosin dynamics on troponin/myosin-free F-actin indicating that tropomyosin moves from the open state toward blocked- or closed-state positions on actin. To follow transitions inherent to tropomyosin itself on F-actin, we performed MD simulations initiated from the blocked-, open-, and intermediate-state models and followed tropomyosin over the surface of F-actin in the absence of myosin and troponin. These MD simulations maintain tropomyosin in a cable-like conformation, including the tropomyosin overlap domain, while allowing tropomyosin to retain most of its motional freedom. Tropomyosin shows considerable azimuthal movement away from the open state toward the surrounds of a more energetically favorable blocked B-state position over F-actin. In contrast, little movement away from the B-state location is observed. Our results are consistent with previous predictions based on electrostatic interaction energy landscapes determined by rigid-body translocation of tropomyosin. They support the view that in the absence of myosin, i.e., when myosin cross-bridges detach from actin, the blocked- or closed-state positions of tropomyosin are energetically favored, while the open state is not.
Published November 15, 2018
Gesehen am 04.06.2019